CO2-triggered reversible phase transfer of graphene quantum dots for visible light-promoted amine oxidation. Issue 7 (6th February 2020) - Tu, Xianjun; Wang, Qin; Zhang, Feng; Lan, Fang; Liu, Hongbo; Li, Run
Abstract : Graphene quantum dots with switchable phase transfer for photocatalytic imine synthesis under visible light. Abstract : Carbon dots, emerging as novel photoluminescent nanomaterials, have attracted increasing attention for photocatalytic applications such as hydrogen evolution, carbon dioxide reduction, pollutant degradation and organic synthesis. However, the separation of carbon dots from the reaction system is always a cumbersome process, which may limit their applications in photocatalysis. Herein, we report the synthesis of a graphene quantum dot with CO2 -switchable reversible phase transfer performance via a facile surface functionalization approach. The mechanism of this hydrophilicity and hydrophobicity alteration involves the protonation–deprotonation transformation and reversible formation of hydrophilic bicarbonate salts when CO2 is bubbled and removed. Then, the obtained graphene quantum dot was utilized as a visible-light photocatalyst for the oxidative coupling of amines. Our photocatalyst demonstrates excellent catalytic efficiency with both high reaction conversion and selectivity. Furthermore, the proposed graphene quantum dot could be recycled via a simple CO2 bubbling method.